2001
DOI: 10.1021/ma0102870
|View full text |Cite
|
Sign up to set email alerts
|

Topographical Nanostructure Patterning on the Surface of a Thin Film of Polyurethane Containing Azobenzene Moiety Using the Optical Near Field around Polystyrene Spheres

Abstract: An indented nanostructure was formed on the surface of azobenzene-functionalized polyurethane thin films by the induced migration of polymer chains using the optical near field generated around polystyrene (PS) spheres. The PS spheres, which had a diameter ranging from 98 to 990 nm, were arranged on the surface of a photoresponsive polymer film using a self-organization process, and the films were then exposed to a linearly polarized Ar+ laser at 488 nm. A hexagonal array of indentations reflecting the origina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 81 publications
1
29
0
Order By: Relevance
“…Polyurethanes and polyureas (PUs) form an important family of industrial polymers that have been widely used due to their good properties such as elasticity, flexibility, thermal stability, and excellent chemical resistance 52–58. In addition, PU conducting polymers have recently been developed59–61 and applications of PUs on PLED have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Polyurethanes and polyureas (PUs) form an important family of industrial polymers that have been widely used due to their good properties such as elasticity, flexibility, thermal stability, and excellent chemical resistance 52–58. In addition, PU conducting polymers have recently been developed59–61 and applications of PUs on PLED have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Azo‐containing polymer systems include polymer matrices doped with azo dyes4, liquid crystalline azo polymers5, 6, Langmuir–Blodgett films7, 8 and amorphous azo polymers9 in which the azo benzene groups are attached to the polymer main chain directly or as side groups. A large number of polyamides10–12 and polyurethanes13–20 with azobenzene groups either in the main chain or as pendant groups have been studied.…”
Section: Introductionmentioning
confidence: 99%
“…We found that the surface of a polymer containing an azobenzene (azopolymer) can transform along with the surface of an attached object by means of irradiating blue light (Kawata et al 1999;Ikawa et al 2000Ikawa et al , 2001Ikawa et al , 2006Hasegawa et al 2001). Figure 13.1 shows the chemical structure of a typical azopolymer.…”
Section: Principles Of Molecular-imprinting and Immobilizationmentioning
confidence: 99%